Annual Health Expenditures by Body Mass Index Categories and the Economic Impact of Obesity in Türkiye: A Retrospective Modeling Study - Ergun Oksuz; Simten Malhan; Halil Alis; Dilek GogasYavuz; Tarkan Karakan; Mehmet Sargin; Alper Sonmez; Lale Tokgozoglu; Batu Gurser; Esra Safak Yilmaz; Volkan Demirhan Yumuk (Obesity Facts)
Introduction: Obesity is considered not only a public health issue on a global scale but also a disease adversely affecting the world economies. Economic impact of overweight and obesity has not yet been investigated in Türkiye at a national level. This study aimed to investigate the impact of obesity on healthcare costs in Türkiye and to estimate the overall national economic burden of obesity. Methods: The study was based on a cross-sectional analysis of retrospectively pooled data from 2009 to 2014 payer claims data and 2014–2019 Türkiye Health Survey (THS). In the first step, obesity-related annual per person overall health expenditures in adults with obesity were calculated and calculations were also made in subgroups of payer and healthcare categories. In the second step, using the developed model, the national economic disease burden of adult obesity was estimated, along with the projections for the estimated expenditures over the next 30 years. Economic values were adjusted according to US dollar values of 2021 purchasing power parities (PPPs) (PPP 1.0 = 2.782 TRY). Results: The annual healthcare costs were significantly higher in individuals with obesity than in those with normal body mass index (BMI) (odds ratio 1.243; 95% confidence interval: 1.206–1.281), and the cost increment was positively correlated with higher BMI (by 117% in class I obesity vs. 169% in class III obesity, p < 0.001). In the year 2021, obesity-related direct and indirect costs in adults were estimated to be PPP 27.4 billion and 39.5 billion, respectively. The total economic burden was estimated to be PPP 66.9 billion, which is equivalent to 2.6% of gross national product. Direct medical cost of obesity corresponds to 8.4% of total health expenditure in Türkiye. Conclusions: Obesity is both an individual and social health problem, which emphasizes the potential role of a range of stakeholders, besides the health sector, in addressing this problem. The indirect costs comprise the key cost driver of the total national cost of obesity, which forms the rationale for population-wide policy interventions toward prevention or reduction of obesity.